Editorial de la revista número 3 del año 2020 - Alfie, José (Revista del Hospital Italiano de Buenos Aires, 2020)
Eduardo Distéfano and collaborators analyze the use of noninvasive ventilation as a method for discontinuing invasive mechanical ventilation in the adult ICU of Hospital Italiano de San Justo. María Graciela Rezzónico and collaborators describe the results of the oral health promotion program implemented at the San Pantaleón Family and Community Medicine Center. Ester Gabriela Scheinfeld, Soledad Lovazzano, and María Fernanda Ramajo describe the endocrine adverse effects of oncologic immunotherapy. Adriana M. Carlucci and collaborators evaluate the contributions of biotechnology to the management of chronic kidney disease and associated anemia. Pablo Rosón and collaborators describe the diagnostic methods used to identify SARS-CoV-2 infection, including molecular techniques for virus identification, serological tests, and their clinical interpretation. Alfredo Eymann and collaborators surveyed recently graduated physicians to identify the factors they value when choosing the institution where they will complete their residency training. In light of advances in health care, curricular designs for the training of future professionals must respond to current demands. Julia C. Saulino and collaborators describe the experience of planning teaching activities within an integrated curriculum. Mariano Kovadloff describes treatment strategies for diabetes in older adults in the context of the COVID-19 pandemic. Telemedicine has shown exponential growth, channeling a large proportion of the hospital’s outpatient care. María Florencia Grande Ratti and Santiago Andrés Frid comment on their recent publication regarding the teletriage experience. Chest radiography and computed tomography play a fundamental role in the clinical management of COVID-19 disease. Facundo N. Díaz and collaborators describe the characteristics of pulmonary and central nervous system abnormalities observed in these patients through imaging studies. Deciding authorship of a scientific paper can be a source of conflict. Sergio Terrasa, María Lourdes Posadas Martínez, and Diego Giunta review the criteria for defining authorship in a research study. María Lourdes Posadas-Martínez and collaborators present the journal’s publication guidelines, the peer-review process, authorship criteria, conflicts of interest, originality requirements, ethical considerations, and plagiarism.